Methodology for developing and evaluating food-based dietary guidelines and a Healthy Eating Index for Ethiopia: a study protocol - Bekele, T.H.; Vries, J.J.H.M. de; Trijsburg, L.; Feskens, E.; Covic, Namukolo M.; Kennedy, G.; Brouwer, Inge D. (BMJ, 2019)
Food-based dietary guidelines (FBDGs) are used to promote and maintain healthy eating in a population, by providing country-specific guidance. However, many African countries like Ethiopia do not have FBDGs. This paper describes the methodology for the development of Ethiopian FBDGs and for creating and evaluating a Healthy Eating Index and a scoring tool that can be used to monitor the adherence of the population to FBDGs.